Fotografi Bayi dan Anak Kecil - Gunawan, Agnes Paulina; Wijaya, Hanny (Humaniora, 2014)
Expression of a baby and a child really is a beautiful moment for a photographer. In fact, some may even call it a miracle to be able to shoot that expression. This is possible since people, that is, the parents, the photographer, and person who is looking at the picture, can be amazed and impressed by the mood and any expression coming from the baby's face or body language. As a baby and a little child, it is as if they have their own world that cannot be touched an adult. This so-called world is what makes it so special and so exclusive, because there in no pressure or choreograph for them. There is only a certain approach that needs to be taken in order to be close to their world. With that said, capturing a child's expression in his world into a picture is also somewhat different. We have to use their version of approach and because of that, baby and kid photography has its own challenges.